Selection of Quality Indicators to Evaluate Quality of Care for Patients with Esophageal Atresia Using a Delphi Method - Teunissen, Nadine M.; Brendel, Julia; Heurn, L.W. Ernest van; Ure, Benno; Wijnen, Rene; Eaton, Simon; on behalf of the EPSA|ERNICA Registry Group; the EA Quality of Care Initiative (European Journal of Pediatric Surgery, 2023)
Objective Survival of neonates with esophageal atresia (EA) is relatively high and stable, resulting in increased attention to optimizing care and longer-term morbidity. This study aimed to reach consensus on a quality indicator set for benchmarking EA care between hospitals, regions, or countries in a European clinical audit.Methods Using an online Delphi method, a panel of EA health care professionals and patient representatives rated potential outcome, structure, and process indicators for EA care identified through systematic literature and guideline review on a nine-point Likert scale in three questionnaires. Items were included based on predefined criteria. In rounds 2 and 3, participants were asked to select the five to ten most essential of the included indicators.Results An international panel of 14 patient representatives and 71 multidisciplinary health care professionals representing 41 European hospitals completed all questionnaires (response rate: 81%), eventually including 22 baseline characteristics and 32 indicators. After ranking, 10 indicators were prioritized by both stakeholder groups. In addition, each stakeholder group highly prioritized one additional indicator. Following an additional online vote by the other group, these were both added to the final set.Conclusion This study established a core indicator set of twenty-two baseline characteristics, eight outcome indicators, one structure indicator, and three process indicators for evaluating (quality of) EA care in Europe. These indicators, covering various aspects of EA care, will be implemented in the European Pediatric Surgical Audit to enable recognition of practice variation and focus EA care improvement initiatives.
Keywords: esophageal atresia; quality indicators; clinical audit